Candidatus Accumulibacter phosphatis clades enriched under cyclic anaerobic and microaerobic conditions simultaneously use different electron acceptors. (1st October 2016) - Camejo, Pamela Y.; Owen, Brian R.; Martirano, Joseph; Ma, Juan; Kapoor, Vikram; Santo Domingo, Jorge; McMahon, Katherine D.; Noguera, Daniel R.
Abstract: Lab- and pilot-scale simultaneous nitrification, denitrification and phosphorus removal-sequencing batch reactors were operated under cyclic anaerobic and micro-aerobic conditions. The use of oxygen, nitrite, and nitrate as electron acceptors by Candidatus Accumulibacter phosphatis during the micro-aerobic stage was investigated. A complete clade-level characterization of Accumulibacter in both reactors was performed using newly designed qPCR primers targeting the polyphosphate kinase gene ( ppk1 ). In the lab-scale reactor, limited-oxygen conditions led to an alternated dominance of Clade IID and IC over the other clades. Results from batch tests when Clade IC was dominant (i.e., >92% of Accumulibacter) showed that this clade was capable of using oxygen, nitrite and nitrate as electron acceptors for P uptake. A more heterogeneous distribution of clades was found in the pilot-scale system (Clades IIA, IIB, IIC, IID, IA, and IC), and in this reactor, oxygen, nitrite and nitrate were also used as electron acceptors coupled to phosphorus uptake. However, nitrite was not an efficient electron acceptor in either reactor, and nitrate allowed only partial P removal. The results from the Clade IC dominated reactor indicated that either organisms in this clade can simultaneously use multiple electron acceptors under micro-aerobic conditions, or that the use of multiple electron acceptors by Clade IC is due to significant microdiversity within the Accumulibacter clades defined using the ppk1 gene. Graphical abstract: Highlights: Accumulibacter phosphatis was the dominant PAO in reactors operated under low-DO conditions. These conditions led to an enrichment of Clade IID and IC in an acetate-fed lab-scale reactor. Clade IC was capable of simultaneously using multiple electron acceptors for P uptake. A heterogeneous population of Accumulibacter was found in the pilot-scale system.